Response of Pinus sylvestris L. radial growth to climate change in stands in Left-Bank Forest-Steppe - Koval, I. M.; Voronin, V. O. (Forestry and Forest Melioration, 2019)
Introduction Being extremely sensitive to changes in environmental conditions, Scots pine (Pinus Sylvestris L.) is widely used in dendroclimatology and dendroindicating to find out how climate impacts radial growth. Adaptation strategies aimed at mitigating the effects of global warming on forest ecosystems, such as increasing of stressful droughts, are a topic of keen discussion. Therefore, the study of the pine radial growth is highly relevant. The aim of the research was to reveal the features of the pine (Pinus sylvestris L.) radial growth response to climate change in the middle-aged pure pine stand within the Left-Bank Forest-Steppe. Materials and Methods The research object was a middle-aged pure pine stand of Vasychevsky Forestry which grows on podzolized clay-sandy soil. Standard dendrochronological methods were used in the study. The cores were taken by Presler borer from 20 trees at height 1.3 m. The tree ring width was measured by the HENSON radial increment-measuring device. The COFECHA programme was used for cross-dating, the ARSTAN programme was used for standardization of tree-ring chronologies and the RESPONSE programme was used to determine the relationship between climate and radial growth. Results The years 1975, 1987 and 2013 have been found to be the years of minimal radial growth due to high average temperatures of 1975 and 2013 as well as low winter temperatures of 1987. The years of maximum radial growth (1944, 1957, 1978 and 2004) are characterized by an optimal balance of temperature and precipitation. Relationships between radial pine growth and climatic factors for two periods, namely 1960–1992 and 1985–2017, were identified. In the second period trees became more sensitive to weather stressful conditions due to warming, as evidenced by the results of correlation analysis and response function analysis. A number of considerable coefficients between radial growth and climatic factors increased during the second period. The negative influence of the previous year's temperatures and that of the growing season of the current year on the pine radial growth has increased. The deficit of precipitation in the second period (1985–2017) began a month earlier in the period of vegetation in comparison with the first period (1960–1992) and lasted from March to September. Considerable correlation coefficients between the tree ring indices and climatic factors ranged from weak to average (-0.54 to 0.63). Conclusions Warming has increased sensitivity of pine radial growth to climate change in 1985–2017 compared to that in 1960–1992. Furthermore, radial growth is affected not only by temperatures of growing season of the current year but also by that of the previous one. Precipitation in the second period (1985–2017) began a month earlier during the growing season compared to the first period (1960–1992) and lasted from March to September. 4 Figs., 1 Table, 19 Refs.